THE AGRO-ECOLOGICAL EFFICIENCY OF UTILIZING CUTTING EDGE TECHNOLOGIES IN THE PRODUCTION OF FRUITS AND VEGETABLES - Shaxloxon Dexkanova Sagdiyevna (American Journals, 2025)
The agro-ecological efficiency of utilizing cutting-edge technologies in the production of fruits and vegetables is an emerging field that integrates modern agricultural innovations with ecological sustainability. This study examines the impact of advanced technologies such as precision farming, hydroponics, and genetic engineering on the yield, quality, and environmental footprint of fruit and vegetable production. These technologies have demonstrated significant potential in optimizing resource use, reducing chemical inputs, and improving crop resilience to climate change. However, their adoption requires careful consideration of ecological balance, biodiversity, and long-term sustainability. This research explores the benefits and challenges associated with these technologies, aiming to provide a roadmap for their future integration into agro-ecosystems.
Keywords: Agro-ecological efficiency, cutting-edge technologies, precision farming, hydroponics, genetic engineering, sustainable agriculture, climate resilience, environmental footprint.